Immune Exclusion Is Frequent in Small-Cell Carcinoma of the Bladder. (2nd May 2019) - Mandelkow, Tim; Blessin, Niclas C.; Lueerss, Eva; Pott, Laura; Simon, Ronald; Li, Wenchao; Wellge, Björn; Debatin, Nicolaus F.; Höflmayer, Doris; Izbicki, Jakob R.; Büscheck, Franziska; Luebke, Andreas M.; et al.
Abstract : Small-cell cancer of the urinary bladder is a rare but highly aggressive disease. It is currently unclear whether immune checkpoint therapies that have been approved for urothelial carcinomas will also be efficient in small-cell carcinomas. In this study, we analyzed potential predictors of response including PD-L1 expression and the quantity and location of tumor-infiltrating lymphocytes (TILs) in 12 small-cell and 69 "classical" urothelial cancers by immunohistochemistry. The analysis revealed that small-cell carcinomas were characterized by the virtual absence of PD-L1 expression and an "immune-excluded" phenotype with only a few TILs in the center of the tumor (CT). In small-cell carcinomas, the average immune cell density in the CT (CD3:159 ± 206, CD8:87 ± 169 cells/mm 2 ) was more than 3 times lower than that in the urothelial carcinomas (CD3:625 ± 800, p < 0.001 ; CD8:362 ± 626 cells/mm 2, p = 0.004 ) while there was no significant difference in the immune cell density at the invasive margin (IM) (small-cell carcinomas CD3:899 ± 733, CD8:404 ± 433 cells/mm 2 ; urothelial carcinomas CD3:1167 ± 1206, p = 0.31 ; CD8:582 ± 864 cells/mm 2, p = 0.27 ). Positive PD-L1 staining was found in 39% of urothelial cancers, but in only 8% of small-cell bladder cancer cases (p = 0.04 ). Concordant with these data, a sharp decrease of PD-L1 positivity from >80% to 0% positive cells and of TILS in the CT from 466-1063 CD3-positive cells/mm 2 to 50-109 CD3-positive cells/mm 2 was observed in two cancers with clear-cut progression from "classical" urothelial to small-cell carcinoma. In conclusion, these data demonstrate that small-cell bladder cancer commonly exhibits an immune-excluded phenotype.